Inovasi Aplikasi “Sayang Warga” dalam Meningkatkan Kemudahan Pendataan Warga oleh Kader di Kota Surabaya - Meiregina, Anisya; Widiyarta, Agus (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
A novelty is needed for government administrators and community development to be more effective and efficient. The Surabaya City Government seeks to provide services in managing information accurately. It is necessary to have the role of the community, namely cadres to contribute in conducting survey services for citizen data collection in order to improve the quality of public services in the city of Surabaya. Information from the survey results can be uploaded via the Sayang Warga application. The purpose of this study is to describe the